Evaluation of a new concept to improve and organize clinical practice in nursing education: a pilot-study - Helle Skou Thomsen; Britt Egeris Jørgensen; Jette Kynde Schøtz; Line Muff Bech; Lea Ladegaard Grønkjær (BMC, 2024)
Abstract Background Nursing students may experience clinical practice as unsafe due to the interactions with patients, fear of making mistakes, lack of clinical experience and supervision, which results in anxiety and stress. Thus, interventions to improve and organize the learning environment in clinical practice for nursing students are warranted, and the aim of this pilot-study was to evaluate a new concept of clinical practice in order to get insight on the different initiatives and gain knowledge for further developing. Methods The new concept consisted of nursing students being affiliated to the same department during their clinical practices, reflective supervision, and participation in a self-compassion course. Data was collected using questionnaires and focus group interviews of 17 nursing students, 17 clinical supervisors, and 14 head nurses. A mixed-methods strategy was employed to give the study a pragmatic approach. Finding from the questionnaires and focus group interviews were analyzed separately and then weaved together into themes. Results The results generated four themes: Information and involvement before and during the new concept, Learning outcomes, safety, and well-being, Impact of reflective supervision and self-compassion course, and Transition from study life to working life. In general, the participating nursing students, clinical supervisors, and head nurses had positives experiences regarding the new concept. They felt well-informed, and they experienced that it contributed to a safe learning environment, increased well-being, strengthened the relationship between nursing students and clinical supervisors and healthcare staff at the department, and prepared the nursing students to working life. Conclusion Our results complement the suggestion that improved quality of clinical practice for nursing students is an effective strategy to establish a safe and supportive learning environment that contribute with satisfaction, successful experiences, and attraction of future nurses. However, further intervention studies are needed to compare the effect of the new concept with traditional clinical practice.